The effects of blood flow restriction combined with endurance training on athletes' aerobic capacity, lower limb muscle strength, anaerobic power and sports performance: a meta-analysis - Dong, K.; Tang, J.; Xu, C.; Gui, W.; Tian, J.; Chun, B.; Li, D.; Wang, L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Objective To evaluate the effects of blood flow restriction (BFR) combined with endurance training on aerobic capacity, lower limb muscle strength, anaerobic power, and sports performance to supply effective scientific guidance for training. Two reviewers independently screened the literature, extracted data, and assessed the risk of bias of the included studies. We searched PubMed, Medline, Cochrane, SPORTDiscus and Web of Science databases up to 28 October 2024. Two reviewers independently screened the literature, extracted data, and assessed the risk of bias of the included studies. We calculated the effect size using standardized mean difference values and the random effects model. The results showed a medium effect size on maximal oxygen uptake (VO2max), a large effect size on lower limb muscle strength, a small effect size on anaerobic power and sports performance. In conclusion, while BFR training during endurance training had a significant positive effect on lower limb muscle strength and moderate improvement in VO2max, its impact on anaerobic power and sports performance was relatively small. These findings suggest that BFR training may be effective for enhancing muscle strength and aerobic capacity, but its benefits on anaerobic power and sport-specific performance may be limited. Therefore, it is important to carefully design BFR training programs to target specific outcomes.